Test run of personal heat transfer rate alarm device for firefighter’s protective clothing - Kovalyshin Владимир; Kovalyshin Василий; Pelekh Роман (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2014)
The paper presents statistics on injuries and deaths of firefighters on duty in Ukraine. A mathematical model for determining the heat transfer rate on the different types of model fires is developed. According to the model characteristic curves for determining safe operating distances to the fire are drawn (such conditions as flame height, combustion temperature, torch-like flame front, location of the device sensors, angle of the torch are taken into account). Field testing of individual heat transfer rate alarm devices for protective clothing of different types is held with the involvement of a dummy and a test person. The recommendations for the placement of alarm device are offered. During the field tests all the protective clothing equipped with alarm devices remained undamaged.